Treatment of nephrotic syndrome with anti-CD20 therapies in pregnancy: a case series and review of the literature - Pierre-Alexis Gauci; Marion Cremoni; Jérôme Delotte; Flavia Vocila; Vincent L. M. Esnault; Barbara Seitz-Polski; Maxime Teisseyre (Renal Failure)
Membranous nephropathy (MN), focal segmental glomerulosclerosis (FSGS) and minimal change disease (MCD) are autoimmune kidney diseases and the most common causes of nephrotic syndrome. Anti-CD20 monoclonal antibodies are now recommended as first-line therapy for MN. Anti-CD20 monoclonal antibodies are also effective in steroid-dependent or frequently relapsing nephrotic syndrome associated with MCD or FSGS. Many women eligible for these treatments are of childbearing age. The impact of anti-CD20 therapies on pregnancy and fetal outcomes remains uncertain, particularly in glomerular diseases. We describe three cases of patients with glomerular disease treated with anti-CD20 therapies in the context of pregnancy and review the literature.